Structural transformation and inclusive growth: Kuznets' 'developer's dilemma' in Indonesia - Kyunghoon Kim; Arriya Mungsunti; Andrew Sumner; Arief Anshory Yusuf (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
We focus on special characteristics of the manufacturing sector, in terms of employment generation and productivity growth, that enable the rapid, resilient economic catch-up of developing countries. We consider the 'developer's dilemma' and the relationship between manufacturing value added or employment shares and trends in income inequality. In Indonesia, structural transformation was growth-enhancing and economic growth inclusive during the decades before the 1997-98 Asian financial crisis. Since then, structural transformation has become notably less growth-enhancing and inclusive growth outcomes have been mixed. Indonesia's structural transformation pattern has shifted, from 'upgrading industrialization' before the crisis to 'stalled industrialization' afterwards. Both periods saw weak Kuznetsian tension, but patterns of structural transformation and inclusive growth beforehand were more 'benign' than patterns after the crisis. The government has adopted diverse social policy programmes and industrial policies to tackle these twin development challenges. We discuss changes in the political economy of development policymaking since the crisis.
Keywords: D63; I32; O14; O25; 330; structural transformation; inclusive growth; Indonesia; industrial policy; social assistance